1984
DOI: 10.1152/jappl.1984.56.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in blood volume following short-term supramaximal exercise

Abstract: To investigate the role of high-intensity intermittent exercise on adaptations in blood volume and selected hematological measures, four male subjects aged 19-23 yr [peak O2 consumption (VO2max) = 53 ml X min-1 X kg-1] performed supramaximal (120% VO2max) cycle exercise on 3 consecutive days. Each exercise session consisted of intermittent work performed as bouts of 1-min work to 4-min rest until fatigue or until a maximum of 24 repetitions had been completed. Measurements on blood samples were made before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 0 publications
6
38
1
Order By: Relevance
“…These large functional changes appeared to be directly related to change in the filling dynamics of the left ventricle and may not have been observed in a normal population. Additionally, the magnitude of the changes in ýOµ,max were, in fact, similar to those reported for healthy younger subjects with similar short-term training protocols of 1 or 2 weeks (Green et al 1984(Green et al , 1991Convertino, 1991). Green et al (1991) reported a 250 ml min¢ (±110 ml min¢) increase in ýOµ,max in healthy men aged 19-30 years after 10-12 consecutive days of exercise at 59% of pre-training peak ýOµ,max for 2 h day¢.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These large functional changes appeared to be directly related to change in the filling dynamics of the left ventricle and may not have been observed in a normal population. Additionally, the magnitude of the changes in ýOµ,max were, in fact, similar to those reported for healthy younger subjects with similar short-term training protocols of 1 or 2 weeks (Green et al 1984(Green et al , 1991Convertino, 1991). Green et al (1991) reported a 250 ml min¢ (±110 ml min¢) increase in ýOµ,max in healthy men aged 19-30 years after 10-12 consecutive days of exercise at 59% of pre-training peak ýOµ,max for 2 h day¢.…”
Section: Discussionsupporting
confidence: 79%
“…Haematocrit was corrected (Green et al 1984) and haemoglobin was determined by the Coulter counter method (Coulter STKR). The %ÄPV before (pre) compared to after training (post) was calculated using the equation of Van Beaumont et al (Van Beaumont, 1972) where: %ÄPV = 100Ï[(100 − Hctpre) − 100(Hctpre − Hctpost)]ÏHctpre.…”
Section: Measurementsmentioning
confidence: 99%
“…These cardiac changes did not correlate with the changes in V O 2 peak after the 2 wk of training in the sedentary subjects. Rather, the adaptations of the RV volumes and the RVEF may be a response to an increased blood plasma volume, which has been shown to occur rapidly when starting exercise training (13). However, the findings of the present study mirrored those observed in the large CMR study, where RV volumes of endurance athletes were increased and RVEF was decreased compared with nonathletes (31).…”
Section: Rvffausupporting
confidence: 53%
“…THb may be expected to decrease with HA exercise in NRs because of increased erythrocyte turnover resulting from daily exercise to which they were not accustomed (32). The reduction in THb in WIN and increase in summer is more difficult to explain; differences in diet and nutrition may be involved (35), or perhaps the HA exercises in WIN were more stressful than in SUM when superimposed on a background of relative inactivity for both R and NRs (12).…”
Section: Discussionmentioning
confidence: 99%